Wind energy development in Norway: exploring the emotional landscape - Lundheim, Sigurd Hilmo; Löfström, Erica (Frontiers in Psychology, 2025)
IntroductionIn Norway, despite ambitious goals for a low-carbon society, the extensive extraction of fossil fuels persists, accompanied by widespread climate skepticism. Wind energy is proposed as a solution but faces resistance.MethodsThis study examines the experiences of both developers and opponents of wind energy through qualitative interviews. Using appraisal theory, we classify emotional reactions, finding sadness and disgust as the most prominent negative emotions.Results and discussionAdditionally, fear and frustration were prevalent, reflecting tensions between wind energy and individual values. Emotional reactions vary widely and suggest that opposition to wind energy is multifaceted. Opponents exhibit stronger emotional responses, while developers, representing business interests, show less intense emotions. We identified 23 key triggers for these emotions, which often can be seen as disruptions caused by the development of wind energy. Engagement, comprising cognitive, affective, and behavioral elements, is essential to addressing these conflicts. Early engagement gives stakeholders the opportunity to influence the process, thereby reducing the conflict level. This highlights the need for earlier and more inclusive engagement processes to foster meaningful dialog and uphold democratic principles.